GEASE: device for analyzing professional practices in the humanization of teaching and healthcare (Research, Society and Development, 2020)
This article presents the application of an innovative methodology for training and analyzing the practices of professionals to contribute to the humanization of teaching and the qualification of health care. The principles of the Groupe d'entreinement à l´analyse de Situations Educatives- GEASE and the concept of implication of Institutional Analysis in its Institutional Socioclinical approach in the construction of this device. It aims to reflect on the application of this device in teaching and health service focusing in humanization, making considerations about its possibilities and limitations. The interventions were carried out in universities in Rio de Janeiro for 09 groups, formed by medical students, nursing residents, preceptors, teachers and health professionals, with a total of 141 participants. The results showed aspects where humanized practices to be implemented, need to rethink the process of professional training in health in their communication practices in order to favor interpersonal relationships. As a potentiality of the study, it stands out that the device used was able to favor the trainer and trainees to analyze their practices, bringing nuances of institutional changes, in favor of the humanization of the care. As limitations, we highlight the need to observe a smaller number of participants by groups in order not to compromise the deepening of the themes brought to the debate. The data show that the proposed device constituted a powerful pedagogical instrument to produce humanized practices both in teaching and in health services.